PERBANDINGAN HASIL BELAJAR MENGGUNAKAN SOFTWARE SIMULATION JARINGAN GNS3 DAN PACKET TRACER DALAM MENGATASI KETERBATASAN ALAT PADA KOMPETENSI WIDE AREA NETWORK (WAN) DI JURUSAN TKJ SMK NEGERI 1 LEMBAH MELINTANG - Siska Indrayani; Edidas Edidas; Thamrin Thamrin (Universitas Negeri Padang, 2018)
Problems in this research The media used in the teaching and learning process still has a shortage of the limited physical component in SMK Negeri 1 Lembah Melintang. This study aims to determine the effect of the use of GNS3 on the results of learning network-based broad-based installation of students of class XI TKJ SMK Negeri 1 Lembah Melintang. This type of research is experimental research. class experimentI is class TKJ A using software simulation GNS3 and class experiment II is TKJ B using sotware simulation packet tracer. Technique of collecting data from post-test value, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class experimental I result I get the average value 78.77 and experiment II get average value 75,42. The result of hypothesis calculation at significant level α = 0,05 got tcount> ttable (3,574> 1,688), because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Thus, the hypothesis is accepted that there is a significant comparation to the student learning outcomes using Software GNS3 to the learning outcomes of installation of broad-based network devices on students of class XI TKJ SMK Negeri 1 Lembah Melintang. Keywords: learning outcomes, GNS3, Packet Tracer.